Optional Narratives and Supplemental Storytelling in Behaviour Interactive’s Dead By Daylight Steven Greenwood - Greenwood, Steven (Monstrum, 2022)
This written analysis and the videographic essay it accompanies explore the relationship between narrative and gameplay in Dead by Daylight (DBD). The term “ludonarrative dissonance” has become very popular in video game discourse, referring to situations where the gameplay and narrative of a game seem to be at odds: the story tells you one thing, while the actual gameplay mechanics ask you to do something that doesn’t logically fit with that story. I want to explore how Dead by Daylight creates the opposite phenomenon of ludonarrative harmony, where every gameplay input or choice not only fits within the narrative but actually serves a crucial role in telling it.Match-based, short-form games like DBD often struggle with ludonarrative dissonance. It’s really hard to tell a cohesive, consistent story in a game with short, standalone, multiplayer matches where each match begins and ends in the same place. DBD is a compelling example of a game that manages to find a strong narrative function for its cyclical matchmaking structure. The last section of this analysis makes a case for why this phenomenon is particularly relevant to the horror genre. DBD takes a style of game where narrative is often seen as secondary or optional to the main experience of gameplay and makes a case for the centrality of narrative to the game. I tie this into a similar discussion of horror, exploring how people often see the plots of horror movies as thin excuses for the “real” entertainment, and how these assumptions miss out on the importance of narrative to even horror films whose narrative seems supplementary.